Measurements of Proton Pumping in Arum maculatum Mitochondria - Ishida, Betty K. (1988)
Direct evidence is presented for the lack of a pH change in the medium associated with electron flow along the alternative, cyanide-resistant pathway in Arum maculatum mitochondria. When these mitochondria oxidize succinate via the cytochrome chain, the medium becomes acidified. However, when the main respiratory chain is blocked by cyanide or antimycin A, oxygen consumption continues, but no pH change occurs. This confirms the lack of a charge separation across the membrane, so that phosphorylation cannot be supported during operation of the alternative oxidase.